Examining Curing Efficiency using Neutron Radiography. Issue 27 (December 2018) - Moradllo, Mehdi Khanzadeh; Montanari, Luca; Suraneni, Prannoy; Reese, Steven R.; Weiss, Jason
Many state highway agencies use prescriptive specifications for the curing of concrete bridge decks, pavements, flatwork, or structural elements. For example, concrete pavements are frequently specified to have a curing compound applied shortly after placement and bridge decks typically require seven days of wet curing. These specifications are often based on historical practices that have developed over the last century as opposed to quantitative measurements of performance. New approaches to curing are being introduced which include advanced curing compound formulations or internal curing, for example. However, clear information is not always available as to how this may affect curing requirements. This paper demonstrates the potential to use neutron radiography to quantify the degree of hydration at various distances from the finished surface. It describes how different curing approaches affect cement hydration in terms of both time and distance from the surface. The results show that in a sample exposed to drying after one day the top 12.5 mm (1/2 in) of the mortar was dramatically affected by evaporation, and the degree of hydration in this region was 32% lower than in a 14-day moist-cured sample. Also, the use of superabsorbent polymers increased degree of hydration by about 3.7–7.8% for sealed samples and samples exposed to drying. While these results are preliminary, it is believed by the authors that neutron radiography provides a powerful approach that could be used to determine equivalent curing requirements for new materials.